Inovasi Pengelolaan Air Hujan sebagai Solusi Berkelanjutan Sebagai Alternatif Solusi Pemenuhan Kebutuhan Air Bersih di Gedung Fakultas Teknik Universitas Panca Bhakti Pontianak - Gunawan, Ivan Andri; Widodo, Muji Listyo; Mulki, Gusti Zulkifli (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Clean water access remains a significant challenge in Pontianak City despite high annual rainfall exceeding 3,000 mm. This study aims to design a rainwater harvesting system (RWH) as an alternative source of clean water for the Faculty of Engineering at Universitas Panca Bhakti (UPB). The research employed a mixed-method approach, including field surveys, technical analysis of roof catchment potential, water quality assessment, system design, and financial feasibility using Net Present Value (NPV) and Benefit-Cost Ratio (BCR). The results showed that the building's roof area (571 m ²) with 80% system efficiency could harvest approximately 1,281.32 m ³/year of rainwater, meeting only 18.34% of the building's clean water demand. Due to low pH and nitrate/nitrite contamination, the proposed treatment system includes sand-carbon-zeolite filtration and UV sterilization. Financially, the project resulted in a BCR of 0.76, indicating it is not yet economically viable on its own. However, the system supports UPB's Green Campus 2027 vision by contributing to flood risk reduction, groundwater conservation, and operational efficiency. Future integration with hybrid systems is recommended to enhance sustainability and water resilience on campus.